Souvenir Centers Driving MSME Income Growth in Pekanbaru: Pusat Oleh-Oleh Mendorong Pertumbuhan Pendapatan UMKM di Pekanbaru - Azzahra, Azzahra; Ningsih, Ellyan Sastra (Academia Open, 2026)
General Background: Micro, Small, and Medium Enterprises (MSMEs) are a key driver of economic development and local income generation, particularly through distribution channels that connect products with consumers. Specific Background: In Pekanbaru City, souvenir centers function not only as retail destinations for tourists but also as platforms for distributing local MSME products and promoting regional culture. Knowledge Gap: Previous studies largely focus on general MSME performance using quantitative approaches, with limited attention to the specific role of souvenir centers in local economic ecosystems. Aims: This study aims to analyze the role of souvenir centers in increasing MSME income and to identify obstacles affecting partnership performance. Results: Using a descriptive qualitative approach with in-depth interviews and NVivo analysis, the findings reveal that souvenir centers contribute to MSME income growth by 15–50%, expand market access, support digital promotion, strengthen production capacity, improve product quality and standardization, and provide distribution platforms without initial costs. However, challenges include cash flow constraints due to consignment systems, limited human resources, production capacity issues, incomplete product legality, and competitive pressures. Novelty: This study introduces an independent mapping of souvenir center ecosystems, including location, product diversity, and accessibility, which were previously undocumented. Implications: The findings suggest the need for improved payment systems, legal assistance, and capacity building to ensure sustainable MSME development and provide insights for policymakers and practitioners in strengthening local distribution networks. Highlights• Income gains reach 15–50% through structured retail distribution channels• Market expansion achieved via tourism-based consumer reach• Partnership barriers arise from consignment schemes and operational limitations KeywordsSouvenir Centers; MSMEs Income Growth; Local Distribution Channels; Market Access Expansion; Product Standardization